Síndrome de Burnout, ansiedade e depressão em profissionais de enfermagem que atuam em Unidade de Terapia Intensiva: estudo transversal - Silva, Noemia Santos de Oliveira (2023)
Introduction: For health professionals, caring for a life in suffering and death can cause psychic changes, being identified as an unhealthy job for the entire team involved. In this sense, the daily work of nursing professionals working in intensive care units (ICU) generates feelings that fluctuate, especially due to the severity of the patients treated. Objective: To determine the associations between burnout syndrome, anxiety and depression in nursing professionals working in the Intensive Care Unit. Materials and method: Cross-sectional cohort with a descriptive and quantitative approach. The sample consisted of 164 nursing professionals from a large public hospital and the University Hospital, both in the state of Sergipe. Data were collected between January and April 2023, using a questionnaire containing items for socioeconomic characterization, health and occupational conditions, HADS scale and Maslach Burnout Inventory, to assess anxiety/depression and burnout syndrome, respectively. Categorical variables were described using absolute and relative percentage frequencies. The hypothesis of independence between categorical variables was tested using Pearson's ChiSquare test and Fisher's exact test, the significance level adopted was 5%. Results: Of the 164 interviewees, the majority were female, with a predominant average age of 41.2 years, stable unions (40.9%) and nursing technicians (77.4%). In relation to occupational aspects, the majority were civil servants (52.1%), earned up to two minimum wages (31.5%), had more than one employment relationship (56.2%), worked up to 43.4 hours per week, reported experiencing pressure at work (40.7%) and dealing with death and suffering (78.5%). In the HADS-a assessment, it was observed that 11.6% of professionals are likely to develop an anxiety disorder. Regarding the HADS-d scale, it is clear that 69.5% are likely to develop depression. Regarding the Maslach burnout Inventory scale, burnout syndrome is present in 47 (28.7%) of professionals.Conclusion: The diagnosis of SAH, smoking, use of casual anxiolytics and antidepressants, employment contracts and suffering pressure at work are predisposing to the development of signs of anxiety and depression. Burnout syndrome showed a significant relationship with housing, education, drug use, anxiety and diabetes mellitus, and the occupational factors predisposing to BS were work overload, dissatisfaction with pay and working conditions and work pressure.